2018
DOI: 10.1186/s40248-018-0150-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors, and impact of lung Cancer on outcomes of idiopathic pulmonary fibrosis: a study from the Middle East

Abstract: BackgroundNo studies have addressed the impact of lung cancer (LC) on prognosis of patients with idiopathic pulmonary fibrosis (IPF) in Upper Egypt. We aimed to evaluate the prevalence and risk factors for LC among IPF patients and its impact on their outcomes and survival in Upper Egypt.MethodsA total of 246 patients with IPF who had complete clinical and follow up data were reviewed. They were categorized into 2 groups: 34 patients with biopsy-proven LC and IPF (LC-IPF) and 212 patients with IPF only (IPF). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This is of particular importance because almost all chronic respiratory disorders affect -in a way or another- the lung mechanics and/or the ventilatory control [ 20 ], so the preparation for weaning a patient with chronic respiratory disorder is of crucial importance and represents a challenging task for the pulmonologist and/or the intensivist. This task will be harder in patients with combined respiratory disorders (e.g., overlap syndrome, obesity hypoventilation syndrome) [ 9 , 20 , 21 ]. Our study included considerable numbers of patients with different respiratory disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This is of particular importance because almost all chronic respiratory disorders affect -in a way or another- the lung mechanics and/or the ventilatory control [ 20 ], so the preparation for weaning a patient with chronic respiratory disorder is of crucial importance and represents a challenging task for the pulmonologist and/or the intensivist. This task will be harder in patients with combined respiratory disorders (e.g., overlap syndrome, obesity hypoventilation syndrome) [ 9 , 20 , 21 ]. Our study included considerable numbers of patients with different respiratory disorders.…”
Section: Discussionmentioning
confidence: 99%
“…However, most lung cancer patients are diagnosed at an advanced stage, and their 5-year survival rate is only 19.7%, that is to say, they missed the best treatment opportunity [ 1 , 3 ]. Most studies have suggested that the occurrence of lung cancer is related to environmental factors, such as smoking, occupational exposure, and air pollution [ 4 , 5 ]. At the same, genetic factors play an important role in the development of lung cancer, including EGFR [ 6 ], CHRNA5 [ 7 ], CLPTM1L [ 8 ], TP63 [ 9 ], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…In China, LC also has a high incidence and mortality, and its morbidity and mortality in men are more than twice that of women [ 6 ]. Most studies have suggested that the occurrence of LC is associated with environmental (smoke, occupational exposure, and air pollution) and genetic factors [ 7 , 8 ]. In particular, genetic factors play an essential role in the occurrence of LC.…”
Section: Introductionmentioning
confidence: 99%